Dietary Methionine Requirement for Growth of Juvenile Humpback Grouper (Cromileptes altivelis) - Nyoman Adiasmara Giri; Ketut Suwirya; Muhammad Marzuqi (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2006)
An experiment to find out amino acid methionine requirement for growth of juvenile humpback grouper has been conducted in 18 polycarbonate 100 L tanks. Each tank was equipped with flow-through water system. Twelve juveniles of humpback grouper (5.6 ± 0.7 g each) were randomly selected and stocked in each tank. Juveniles humpback grouper for the experiment were purchased from back yard hatchery in Gondol. Fish fed test diets twice everyday at satiation level for 49 days. Test diets were prepared as dry pellet with casein and fish meal as the intact protein sources, supplemented with the mixture of crystalline L-amino acids to correspond to the amino acid pattern found in the whole body protein of the juvenile humpback grouper, except methionine. Basal diet (diet-1) containing 0.86% methionine was supplied from casein and fish meal. Graded level (0.3%) of L-methionine was added to the basal diet to get the final methionine level in each test diet of 0.86%, 1.16%, 1.46%, 1.76%, 2.06%, and 2.36 %. The experiment was designed according to completely random design (CRD) with 6 treatments (methionine levels) and three replicates for each treatment. Result of the experiment showed that dietary methionine content influenced final weight, weight gain, specific growth rate, feed efficiency, protein retention, and body protein content of juvenile humpback grouper. Optimum dietary methionine for juvenile humpback grouper was calculated using broken line regression analysis. Optimum dietary methionine requirement for growth of juvenile humpback grouper was 1.18% (2.41% of dietary protein) and 1.16% (2.37% of dietary protein) based on weight gain data and feed efficiency, respectively.